Purification and Characterization of a Novel Thermostable Papain Inhibitor from Moringa oleifera with Antimicrobial and Anticoagulant Properties - Juliana Cotabarren; Santiago Claver; Juan Abreu Payrol; Javier Garcia-Pardo; Walter David Obregón (MDPI AG, 2021)
Plant cystatins (or phytocystatins) comprise a large superfamily of natural bioactive small proteins that typically act as protein inhibitors of papain-like cysteine proteases. In this report, we present the purification and characterization of the first phytocystatin isolated from Moringa oleifera (MoPI). MoPI has a molecular mass of 19 kDa and showed an extraordinary physicochemical stability against acidic pHs and high temperatures. Our findings also revealed that MoPI is one of the most potent cysteine protease inhibitors reported to date, with Ki and IC50 values of 2.1 nM and 5.7 nM, respectively. More interestingly, MoPI presents a strong antimicrobial activity against human pathogens such as Enterococcus faecalis and Staphylococcus aureus. In addition, MoPI also showed important anticoagulant activity, which is an unprecedented property for this family of protease inhibitors. These results highlight the pharmaceutical potential of this plant and its derived bioactive molecules.